Levels and enantiomeric signatures of organochlorine pesticides in Chinese forest soils: Implications for sources and environmental behavior - Zheng, Qian; Li, Jun; Wang, Yan; Lin, Tian; Xu, Yue; Zhong, Guangcai; Bing, Haijian; Luo, Chunling; Zhang, Gan (Environmental pollution (1987), 2020)
We investigated the levels and distributions of organochlorine pesticides (OCPs) in 159 background soil samples collected from 30 forested mountain sites across China. The sum of DDT was the most abundant OCP, with the concentrations of 0.197–207 ng/g and 0.033–122 ng/g in the O-horizon and A-horizon, respectively. High concentrations of OCPs usually occur near agricultural regions or high consumption areas. The spatial distribution was mainly influenced by the emission sources and soil total organic contents (TOC). The chiral compounds were generally nonracemic in the soils and showed preferential degradation of (−) o,p′- dichlorodiphenyltrichloroethane, (+) trans-chlordane, and (−) cis-chlordane in both the O- and A-horizons. The enantiomeric fraction (EF) distributions of chiral OCPs displayed no differences across the forest sites in the O-horizon or the A-horizon. Comparing the deviation of EFs from racemic (DEVrac = absolute value of 0.500 - EF) with environmental parameters, we found that DEVrac of cis-chlordane demonstrated a strong positive correlation with TOC (p < 0.05) and the C/N ratio (p < 0.01). This relationship suggests that these factors could affect the microbial activity and significantly impact the extent of enantioselective degradation of chiral compounds in the soils. Fresh and historical applications of DDT and historical chlordane and endosulfan uses may be prominent sources of OCP accumulation in Chinese forest soils. [Display omitted] •Source and TOC influence the OCP distribution across Chinese 30 mountain sites.•We found ubiquitously non-racemic proportions of chiral OCPs.•SOC and C/N ratio may affect the enantioselective degradation of chiral OCPs.•Fresh input and historical applications of DDTs are both important sources in soils.•Chlordane and endosulfan in soils are primarily from historical residue. Sources and total organic contents (TOC) could influence the distribution of OCPs, while TOC and the C/N ratio could affect the degradation of chiral compounds.